Efficacy and Safety of Carbetocin in Prevention of Postpartum Hemorrhage - Nida Arif, Umber Arooj Tahir, Komal Aftab, Tahreem Rasheed, Khushboo Chandio, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The study compared the effectiveness of carbetocin and oxytocin, administered post caesarian section for prevention of postpartum haemorrhage (PPH). Study Design: This was a prospective single center, case-control, cross sectional, observational, double ended study conducted from September 2020 to January 2022, comprising 150 female patients. Methods: The study was conducted at Hameeda Memorial Hospital Lahore in women undergoing caesarean section under regional and general anesthesia. Women were randomized to receive either carbetocin or oxytocin 5 IU intravenously. Results: Average age of patients was 34.5 years with average BMI of 27. It was noted that patients who were administered drugs had 348.6ml less blood loss than those not administered in PPH. Patients who did not received the drugs had average 800 ml blood loss. Whereas those who did had the drug had average of 451ml loss of bleed in PPH. Carbetocin showed effectiveness in preventing PPH by maintaining uterine tone. It was found that it significantly reduced the need for additional uterine contractile interventions to prevent or treat excessive bleeding after cesarean. In high-risk women, carbetocin has been found to be more effective than oxytocin in preventing blood loss greater than 500 mL during the cesarean section. Practical Implication: This study will help the gynecologists in selecting potent and safe therapeutic agents for the prevention of postpartum hemorrhages in high risk females. Conclusion: Carbetocin has been shown to be a safe and effective option for the prevention of postpartum hemorrhage in high-risk women as compared to other therapeutic agents along with potential safety margins. Keywords: Carbetocin, efficacy, safety, prevention, postpartum hemorrhage, oxytocin, uterotonic